Impact of chronic lymphocytic leukaemia on melanoma outcomes: A retrospective case‐control study. (14th March 2022) - Jobson, Dale; McCormack, Christopher J.; Mar, Victoria; Tam, Constantine; Henderson, Michael A.
Summary: With new, effective treatments for chronic lymphocytic leukaemia (CLL) the impact of second malignancies is increasingly important. We performed a retrospective case‐controlled study examining the effect of CLL and its treatment on melanoma‐specific survival and recurrence. A total of 56 patients with melanoma with CLL were matched 1:1 to patients without CLL for age, date of diagnosis, gender and melanoma tumour, node, metastasis (TNM) stage. Multivariate analysis found CLL was associated with significantly worse melanoma‐specific mortality (hazard ratio [HR] 2.46, 95% confidence interval [CI] 1.27–4.74, p = 0.007) and recurrence (HR 3.44, 95% CI 1.79–6.63, p < 0.001). Patients with CLL had poor immunotherapy tolerance and prior CLL treatment was not associated with melanoma outcomes.